ANALISIS REINVENTING GOVERNMENT TERHADAP PEMIKIRAN DAN KEBIJAKAN BASUKI TJAHAYA PURNAMA (Januari 2013 – Desember 2014) - -, Suwardi (Transformasi, 2015)
Tjahaya Basuki Purnama (Ahok) Head of Jakarta Special Capital Region efforts led Jakarta lotwith new ideas are widely publicized by mediamassa online. This study analyzes the thinking andpolicy Ahok in managing the bureaucracy of reinventing government (D. Osborn and T. Gabler;1993). The results research showed that Ahok have tend build Jakarta governance in line withthe principle of ten reinventing govermant. The top three concerns highest Ahok first thought wasa statement in the category of anticipatory governance principles (21.92%); Second principle ismission driven government (17.11%); The third principle community owened government(12.30%).Keywords: Ahok; reinventing; Government; Jakarta